The effect of perceived organizational support and psychological capital on OCB: mediating role of engagement - Muhammad Ali Ansori; Nury Ariani Wulansari (Diponegoro International Journal of Business, 2021)
This paper aims to investigate the effect of psychological capital (PsyCap) as an intrinsic factor and perceived organizational support (POS) as an extrinsic factor on OCB and to verify the mediating role of work engagement (WE) in the relationship of PsyCap, POS and OCB. The population in this study are state university lecturers especially at Universitas Negeri Semarang. Using proportionate random sampling technique, the data was collected from 145 lecturers. The structural equation model-partial least square (SEM-PLS) was used to test the hypotheses with analysis tools in the form of SmartPLS 3.0. The result showed that PsyCap had a positive and significant effect on work engagement and OCB, then POS had an insignificant effect on OCB and work engagement. The result found that work engagement has a mediation effect in the relationship between PsyCap and OCB. This study also showed that PsyCap as an intrinsic factor is considered more capable than POS as an extrinsic factor to improve lecturer’s OCB. It is highly recommended for the organization to focus on lecturer’s psychological capital investment, because lecturer’s PsyCap will be directly affect to lecturer’s positive behaviour such as work engagement and OCB.